(untitled) (Progressive Agriculture, 2016)
An investigation was carried out to the assessment on thunderstorm and lightning and their impact on human health, agriculture and fisheries. More than half of the respondents (58%) were illiterate and lack of knowledge about thunderstorm (Melandaha Upazila) and 30% were illiterate in Mymensingh Sadar Upazila. In Mymensingh Sadar Upazila, about 70% respondents suffered with light dumb disease and about 46% respondents suffered with moderate headache disease. About 40% respondents suffered with severe heart failure disease. In Melandaha Upazila, about 42% respondents suffered with light heart failure and neural damage disease. About 28% respondents suffered with moderate skin irritation and headache disease. About 32% respondents suffered with severe heart failure and neural damage disease. In Mymensingh Sadar Upazila, about 53% of the respondents reported that fishes are at risk condition at the time of Thunderstorm and lightning and about 47% of the respondents reported that fishes were at very risk condition during TS and lightning. In Melandaha Upazila, about 67% of the respondents reported that fishes were at risk condition at the time of TS and lightning and about 33% of the respondents reported that fishes were at very risk condition during TS and lightning. Most of the respondents reported that TS affected the agricultural production very much. For TS and lightning, agricultural land was unsuitable for agricultural production. Trees and crops were uprooted, damaged and fired. So, people lose their property and lose to their lives. Farmers were struck by thunderbolt while they were working at paddy field and harvesting paddy field. Routine research work with wide public awareness, government and NGO participation, and government regulation are needed for safe and sound environment. Progressive Agriculture 27 (1): 57-63, 2016